Wave climate analysis for shoreline management plan in Kelantan, Malaysia - Yusoff, M A M; Al-Qadami, E H H; Razi, M AM; Wang, M; Daud, Z H; Mokhtar, A; Mahamud, M (2023)
Waves climate analysis is of primary concern for several purposes such as maintaining coastal structures, navigation and maritime operations, coastal management, and recreation and tourism. Therefore, understanding the wave climate of a particular region helps in making informed decisions related to coastal and maritime activities, ensuring safety, efficiency, and sustainability. In this paper, wave analysis was conducted for Kelantan State shoreline, Malaysia. The studied shoreline covers around 71 km starting from Pengkalan Kubur to Besut. 5 years data (2014 to 2019) was collected at the location of 6.3N and 102.3E. The analysis was performed under different aspects including, annual wave rose, annual percentage reoccurrence, return period analysis, and closure dept. According to the results, it was found that the predominant waves are coming from the 60 to 90 degrees North sector due to the unlimited fetch in that direction. Besides it was noticed that more than 50% of the waves have periods between 4 to 7 seconds and around 52% have wave heights of less than 1.5m. Also, it was found that the wave depth for a 100-year return period is about 2.75m. Finally, the depth of closure was calculated and found to be 7 m. The outcomes of this study can provide a better understanding of the wave climate along the Kelantan State shoreline and can be used as a reference for future coastal and maritime activities